An innovative joint connecting beam for precast concrete shear wall structures. (December 2016) - Lu, Xilin; Wang, Lu; Wang, Dun; Jiang, Huanjun
Abstract: The precast shear wall structure has outstanding features for green buildings due to its construction convenience, safety, high quality and low pollution. In general, precast concrete shear walls are connected by multiple joints. The joint between precast walls has very strong influence on the whole structure, which calls for more detailed investigation. A new kind of connection – the joint connecting beam – was developed to connect the vertical reinforcement in precast concrete shear wall structures. This innovative connecting method has the advantages of convenient operation and saving steel. To evaluate the performance and for better application of the joint connecting beam, an experiment on seven full‐scale specimens was conducted under cyclic loading, including two cast‐in‐situ walls and five precast walls with varying reinforcement and sectional heights of the joint connecting beam. A comparison was performed between cast‐in‐situ walls and precast walls with joint connecting beam, focusing on failure mode, hysteretic curve, skeleton curve, bearing capacity, ductility and energy‐dissipating capacity. The results show that the joint connecting beam can effectively transfer the load of precast walls, especially for squat precast walls. Moreover, finite element models were developed to simulate the performance of the specimens. The simulation results agree well with experimental results.